E-CRM System Development Strategy As An Effort To Improve Computer Services And Sales - Azmi Ainul Rifky; Herman Saputra; Elly Rahayu (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2026)
The rapid development of digital technology has significantly influenced business strategies and customer behavior, particularly in the context of service and sales management. However, many businesses still face challenges in managing customer data that is not integrated, which affects service quality and marketing effectiveness. This study aims to design and implement an Electronic Customer Relationship Management (E-CRM) system to improve customer service and sales performance. The research method used is descriptive analysis with data collection conducted through observation and interviews to identify system requirements and existing problems. The system was developed using a web-based approach to integrate customer data, transaction history, and communication processes. The results show that the implemented E-CRM system is able to improve customer data management, facilitate customer behavior analysis, enhance service responsiveness, and support more targeted marketing strategies. In addition, the system contributes to increasing customer satisfaction and loyalty through better interaction and personalized services. In conclusion, the development of a web-based E-CRM system provides an effective solution for optimizing customer relationship management and improving business competitiveness in the digital era.